Currículo-planta: a form(a)ção da semente e sua utilização na educação tecnológica - Peres, Janaina Campos (2024)
One of the main debates in the field of Education involves the curricula. They are often taken as a mere set of contents that must be learnt while the students are at school. Many professionals who have the responsibility of developing the curricula do not seem to understand their deep significance. Thus, they end up failing to come up with curricula aligned with contemporary educational needs. Could this be linked to certain guiding discourses in the development of curricula? Or to deficiencies in teacher training? It is also debated if, when it comes to discourse, the act of reluctantly and deficiently writing curricular texts – which are often unclear when it comes to the needs and expectations of the school community – brings forth documents that are just obsolete. Our research examines the process of developing and implementing curricula through training axes in the field of Natural Sciences, within Biology studies, having High School and professionalizing Technology Education (EPT) as its empirical context in an autonomous educational institution in the of the State of São Paulo, Brazil. We have turned the curricular discourses addressed here in vegetal metaphors, permeated by post-critical ideas and based on concepts from thinkers such as Gilles Deleuze and Félix Guattari, conceived as a “rhizome of agencies” constituting the dynamics of curricula. The use of metaphors is an opportune and resourceful device for academic thinking, as supported by Michel Maffesoli. This research has a qualitative nature. It was carried out through empirical observation and direct participation in meetings with the school’s curricular management team, as well as by analyzing documents such as the São Paulo Curriculum (2019), the Common National Curricular Base (2018), the National Curricular Parameters (2006) and Course Plans already approved by the institution (2015, 2019, 2021, 2022). The choice of these documents was due to the fact that the author of this research has been part of the institution's curriculum management team since 2021. The curricular base at the referred institution is quite traditional, basically focused on skills for competing for jobs in the market. The development of curricula features mistakes and flaws due to variables such as the lack of work time, the lack of qualifications, undersized teams, and a high turnover. The implementation of curricula is sometimes hasty and confusing, which results in these documents being misunderstood by teachers and students. This led subsequently to the partial abandonment of what had been published in 2022.